The Performance Of Initial Public Offer Versus Performance Of Privatised Government Companies - Mohamad Tenang, Zambri (1998)
This study, however, has three major objectives. First, to determine the general trends of underpricing of IPO's from 1987 to 1997. This is because there is a general trend that IPO's has become popular among investors in Malaysia. The second is t0 determine the possible factors that might have contributed to the level of low price bow. Thirdly, to compare the general trends against privatised government companies.